2015
DOI: 10.1002/adma.201405783
|View full text |Cite
|
Sign up to set email alerts
|

Chlorine Resistant Glutaraldehyde Crosslinked Polyelectrolyte Multilayer Membranes for Desalination

Abstract: Crosslinked polyelectrolyte multilayer membranes are synthesized with salt rejection values approaching those of commercial desalination membranes, but with increased chlorine resistance. The membranes are fabricated directly onto porous commercial substrates. Subsequent crosslinking of the polycation layers with glutaraldehyde leads to NaCl rejections of up to 97%, while the incorporation of a highly sulfonated polysulfone polyanion leads to high chlorine resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(67 citation statements)
references
References 48 publications
(15 reference statements)
1
64
0
Order By: Relevance
“…It is widely acceptedt hat cross-linkinga lways results in low membrane swelling and high ion rejection. [37,38] In this study, prolonged chemical cross-linking time led to an increasei ns alt rejection but ad ecrease in water permeation flux in the first 4h because the long cross-linking time resultsi nahigh degree of cross-linking( Figure 4b). The nanofiltrationp erformance changes only slightly with longer cross-linking time, as the reaction was mostly completed in 4h.T herefore, the optimized fabrication conditions were determined to be contra-diffusion for 5min followed by cross-linking for 4h.…”
Section: Performance Of the Alginate Tfc Nfmsmentioning
confidence: 53%
See 1 more Smart Citation
“…It is widely acceptedt hat cross-linkinga lways results in low membrane swelling and high ion rejection. [37,38] In this study, prolonged chemical cross-linking time led to an increasei ns alt rejection but ad ecrease in water permeation flux in the first 4h because the long cross-linking time resultsi nahigh degree of cross-linking( Figure 4b). The nanofiltrationp erformance changes only slightly with longer cross-linking time, as the reaction was mostly completed in 4h.T herefore, the optimized fabrication conditions were determined to be contra-diffusion for 5min followed by cross-linking for 4h.…”
Section: Performance Of the Alginate Tfc Nfmsmentioning
confidence: 53%
“…It is widely accepted that cross‐linking always results in low membrane swelling and high ion rejection . In this study, prolonged chemical cross‐linking time led to an increase in salt rejection but a decrease in water permeation flux in the first 4 h because the long cross‐linking time results in a high degree of cross‐linking (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…Most of the commercial NF membranes synthesized via interfacial polymerization (IP) are negatively charged during normal aqueous processes. According to the Donnan exclusion, the negatively charged NF membranes tend to exhibit excellent rejection to multivalent anions (e.g., Cr 2 O 7 2 À , SO 4 2 À ) and relatively low rejection to multivalent cations (e.g., Mg 2 þ , Ca 2 þ ) [15,16]. For example, Hilal et al studied the rejection of heavy metal ions using NF270 membrane and the results showed that with all metals examined (except As (III)), when the feed pH is below the isoelectric point at pH around 4, the rejection increased.…”
Section: Introductionmentioning
confidence: 99%
“…6,14 However, oxidation and fouling are currently two major obstacles for the aromatic polyamide RO membranes, which limit further application of RO membrane technology. [15][16][17][18][19][20] To address these two problems, various approaches have been performed including pretreatment of the RO feed solution, development of new membrane materials, surface modication of commercial RO membranes, [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] optimization of process conditions, and periodic cleaning. [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] Even aer long periods of such developments, however, biofouling is still the major reason for performance deterioration of conventional PA membranes including water ux decline and salt rejection reduction.…”
Section: Introductionmentioning
confidence: 99%